A modified Jerusalem microstrip filter and its complementary for low phase noise X-band oscillator - Nimehvari Varcheh, Hamed; Rezaei, Pejman; Kiani, Sina (International journal of microwave and wireless technologies, 2023)
This article shows the design of two different low phase noise (LPN) planar X-band frequency oscillators using two various microstrip filters (MFs). These two MFs act as a frequency stabilization part in the loop of the microwave oscillator. The first one, the modified Jerusalem MF (MJ-MF), is based on the Jerusalem scheme. The second one, the complementary modified Jerusalem MF (CMJ-MF), is complementary of the MJ-MF. Finally, by employing the branchline coupler, the LPN MF oscillator is achieved. The MJ-MF (narrowband filter) LPN X-band oscillator operates at 8.17 GHz and denotes a phase noise (PN) of −161 dBc/Hz at 1-MHz frequency offset. The CMJ-MF (wideband filter) LPN X-band oscillator operates at 8.14 GHz and mentions a PN of −157 dBc/Hz at 1-MHz frequency offset.